Mid-infrared interferometry of the massive young stellar object NGC 3603 - IRS 9A - Vehoff, Stefan; Hummel, C. A.; Monnier, J. D.; Tuthill, P.; Nürnberger, D. E. A.; Siebenmorgen, R.; Chesneau, O.; Duschl, W. J. (Astronomy and astrophysics, 2010)
Very few massive young stellar objects (MYSO) have been studied in the infrared at high angular resolution due to their rarity and large associated extinction. We present observations and models for one of these MYSO candidates, NGC 3603 IRS 9A. Our goal is to investigate with infrared interferometry the structure of IRS 9A on scales as small as 200 AU, exploiting the fact that a cluster of O and B stars has blown away much of the obscuring foreground dust and gas.
Gesehen am 31.08.2023